Serum Sema3A Is in a Weak Positive Association With Bone Formation Marker Osteocalcin But Not Related to Bone Mineral Densities in Postmenopausal Women - Liu, Dong-mei; Lu, Nan; Zhao, Lin; Zhang, Min-jia; Tao, Bei; Xuan, Yan; Sun, Li-hao; Zhao, Hong-yan; Wang, Wei-qing; Liu, Jian-min; Ning, Guang (The journal of clinical endocrinology and metabolism, 2014)
Context:The chemorepellent semaphorin-3A (Sema3A) was shown to favor bone metabolism in mice, but its bone effects in humans are not described.Objective:The aim of the study was to investigate the associations between serum Sema3A, bone biochemical markers, and bone mineral densities (BMDs) in women.Design, Setting, and Participants:This was a cross-sectional study involving 1012 pre- and postmenopausal women.Main Outcome Measures:Fasting serum Sema3A, osteocalcin (Ocn), and cross-linked C-telopeptide of type 1 collagen were measured. Dual-energy X-ray absorptiometry was performed to determine the BMDs at the lumbar spine and femoral neck. History of osteoporotic fractures was reported by the participants.Results:In postmenopausal women (n = 860), a significant positive association between Sema3A and Ocn levels was demonstrated (r = 0.077, P = 0.025) when age was adjusted. The serum Ocn level was significantly higher in the fourth quartile of serum Sema3A as compared with the first quartile (21.09 ± 0.56 ng/mL vs 19.45 ± 0.44 ng/mL, P = .018). Serum Sema3A concentrations were similar in subjects with normal BMD, osteopenia or osteoporosis, and those with and without osteoporotic fractures. Multivariate stepwise regression analysis revealed that cross-linked C-telopeptide of type 1 collagen, body mass index, creatinine, Sema3A, L1–4 BMDs, and age were determinants of Ocn (adjusted R2 for the model = 0.532, P < .001) .Conclusions:The positive correlation between Sema3A and bone formation marker Ocn revealed in this human study partly supports the recently findings in mice studies. However, the general effects of Sema3A on bone metabolism are weak and not clear as evidenced by lack of association between this parameter and BMDs and osteoporotic fractures.